O cuidado humanístico como foco institucional: um estudo sobre empatia dos profissionais de saúde na área obstétrica - Lima, Simone Pedrosa (2006)
Empathy is a basic facilitating element of the therapeutic helping relationship and the humanization process in health care. The objectives of this study were to identify the empathy level of health professionals working in the obstetrical sector of a university hospital recognized for its humanistic care and the perceptions of the women under their care regarding the empathic behavior shown by these professionals during hospitalization. We conducted a quanti/qualitative study with 47 health professionals that worked in the obstetrical sector (13 obstetricians, 12 nurses, 22 nurse technicians) and an intentional sample of 101 women that received cared from these professionals during the study period. We collected data by means of the Jefferson Empathy Scale for Health Professioals (JEPS-HR) and the Patient´s Perception of Health Professional Empathy (PPHPE), and two additional open questions designed to obtain the subjective opinion about the empathic behavior during the care. We utilized thematic analysis for the data obtained through the open questions and descriptive and inferential statistics for the quantitative data. We identified five thematic categories that represent the aspects valued by the professionals in their relationship with the women under their care: emotional involvement, communication, warm environment, integral vision and technical/scientific knowledge. The mean score on the JEPS-HR reported for the health professionals was 120,40, being that the maximum possible was 140.The Cronbach Alpha for the JEPS-HR was 0,83, indicating an acceptable level of reliability for this population. We consider therefore, that these professionals presented an acceptable empathy level when compared to other populations observed with the JEPS-HR. The results also indicated that women had statistically significant (p ≤ 0,05) higher scores than men and that professionals with higher working hours tended to have lower scores in the empathy scale (r = -0,288; p ≤ 0,05). The analysis of the subjective responses of the women indicated that they were satisfied with the humanistic care provided by the professionals but they also point out the existence of some power relationships. There were no significant differences in the empathy level of the medical or nursing team perceived by the women who registered means of 41,90 and 41,20 respectively on the PPHPE. In view of these results and considering the relevance of the element of empathy for care based on humanistic values, we reiterate the importance of further in-service training for the health team of the hospital in focus, on the topics of empathy and global aspects of humanized care for the implementation of its mission